The Impact Of Interactive Experience And Online Service Quality On Customer Satisfaction With The Mediation Of Consumer Value Perception - Miko Andi Wardana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This article explores the intricate dynamics influencing customer satisfaction in the digital commerce landscape, with a specific focus on interactive experiences, online service quality, and consumer value perception. The research reveals significant direct effects, indicating that both interactive experiences and online service quality play crucial roles in shaping consumer value perception, subsequently influencing customer satisfaction. Furthermore, the study uncovers significant indirect effects, illustrating that enhancements in interactive experiences and online service quality not only directly impact customer satisfaction but also exert substantial influence through the mediating role of consumer value perception. The findings highlight the interconnected nature of these factors and emphasize the need for businesses to adopt a holistic approach to optimize overall customer satisfaction. This research provides valuable insights for companies, including those in dynamic markets like PT. Bali Indoraya, guiding them in refining digital strategies and fostering enduring customer relationships in the continually evolving digital commerce landscape. Keywords: Interactive Experience, Online Service Quality, Customer Satisfaction, Consumer Value Perception